Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the equation [tex]\( 11(n - 1) + 35 = 3n \)[/tex] for [tex]\( n \)[/tex], follow these steps:
1. Expand the equation:
[tex]\[ 11(n - 1) + 35 = 3n \][/tex]
Distribute the [tex]\( 11 \)[/tex] inside the parentheses:
[tex]\[ 11n - 11 + 35 = 3n \][/tex]
2. Simplify the left side:
Combine the constants [tex]\(-11\)[/tex] and [tex]\(35\)[/tex]:
[tex]\[ 11n + 24 = 3n \][/tex]
3. Isolate the variable term:
Subtract [tex]\(3n\)[/tex] from both sides to get all the [tex]\(n\)[/tex] terms on one side:
[tex]\[ 11n - 3n + 24 = 0 \][/tex]
Simplify by combining like terms:
[tex]\[ 8n + 24 = 0 \][/tex]
4. Solve for [tex]\(n\)[/tex]:
Subtract [tex]\(24\)[/tex] from both sides to isolate the term containing [tex]\(n\)[/tex]:
[tex]\[ 8n = -24 \][/tex]
Divide both sides by [tex]\(8\)[/tex]:
[tex]\[ n = -3 \][/tex]
Therefore, the solution to the equation [tex]\( 11(n - 1) + 35 = 3n \)[/tex] is:
[tex]\[ n = -3 \][/tex]
1. Expand the equation:
[tex]\[ 11(n - 1) + 35 = 3n \][/tex]
Distribute the [tex]\( 11 \)[/tex] inside the parentheses:
[tex]\[ 11n - 11 + 35 = 3n \][/tex]
2. Simplify the left side:
Combine the constants [tex]\(-11\)[/tex] and [tex]\(35\)[/tex]:
[tex]\[ 11n + 24 = 3n \][/tex]
3. Isolate the variable term:
Subtract [tex]\(3n\)[/tex] from both sides to get all the [tex]\(n\)[/tex] terms on one side:
[tex]\[ 11n - 3n + 24 = 0 \][/tex]
Simplify by combining like terms:
[tex]\[ 8n + 24 = 0 \][/tex]
4. Solve for [tex]\(n\)[/tex]:
Subtract [tex]\(24\)[/tex] from both sides to isolate the term containing [tex]\(n\)[/tex]:
[tex]\[ 8n = -24 \][/tex]
Divide both sides by [tex]\(8\)[/tex]:
[tex]\[ n = -3 \][/tex]
Therefore, the solution to the equation [tex]\( 11(n - 1) + 35 = 3n \)[/tex] is:
[tex]\[ n = -3 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.